Expert System for Diagnosing Diseases in Cats that Can Contagious to Humans Using the Certainty Factor Method: Expert System for Diagnosing Diseases in Cats that Can Contagious to Humans Using the Certainty Factor Method - Ivan Setiawan; Fauziah Fauziah; Andrianingsih Andrianingsih (Institute of Computer Science (IOCS), 2020)
Cats are one of the most popular pet in the world. In addition to adorable, maintenance is not too much trouble is also a reason that makes this animal rage. However, the way poor maintenance can make a cat exposed to various diseases. Some diseases in cats can even be transmitted to humans. For this reason, research was undertaken to design an expert system to diagnose the disease in cats that can be transmitted to humans using the method of Certainty Factor, so that the cat's owner can recognize the symptoms of the disease in cats peliaharaannya. Black box testing results show that the features of the application has been running well. While the validity of the test showed that the data are in accordance with the reference books.